2021
DOI: 10.1016/j.crphar.2021.100043
|View full text |Cite
|
Sign up to set email alerts
|

Screening of phytoconstituents of Andrographis paniculata against various targets of Japanese encephalitis virus: An in-silico and in-vitro target-based approach

Abstract: Japanese encephalitis (JE) is one of the viral diseases affecting millions of peoples across the globe specifically developing countries. There is no specific treatment available, however, vaccines are available for its prevention. Unfortunately, available vaccines are not effective against all clinical isolates and are also associated with neurological complications in some individuals. We have screened the selected phytoconstituents of Andrographis paniculata against various targets of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…In drug discovery pipelines, medicinal plants have become the popular source of natural compounds with high structural diversity against viral infections [ 39 , 40 , 41 , 42 , 43 ]. Several medicinal plants or natural compounds have shown promising effects against JEV [ 33 , 44 , 45 , 46 , 47 ]. Echinacea angustifolia ( E. angustifolia ) is one of the most well-known medicinal plants in its genus, which has been studied for medicinal properties, including antibacterial, anti-inflammatory, and antiviral activity properties [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…In drug discovery pipelines, medicinal plants have become the popular source of natural compounds with high structural diversity against viral infections [ 39 , 40 , 41 , 42 , 43 ]. Several medicinal plants or natural compounds have shown promising effects against JEV [ 33 , 44 , 45 , 46 , 47 ]. Echinacea angustifolia ( E. angustifolia ) is one of the most well-known medicinal plants in its genus, which has been studied for medicinal properties, including antibacterial, anti-inflammatory, and antiviral activity properties [ 48 , 49 , 50 , 51 , 52 , 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 Docking studies are widely used to predict the energetically favored binding conformation of ligand in the active site of the target. 27 The results of the current investigation have indicated the involvement of HLA*B1502, HLA*B5801, and HLA*B5801 in the antiviral drugsinduced DRESS syndrome. However, the HLA is not the only and determining factor in the pathogenesis of DRESS.…”
Section: Discussionmentioning
confidence: 63%
“…The ADMET analysis was carried out by using the pkCSM online web tool and the compound was shown to have a good pharmacokinetic and safety profile of Andrographolide. In addition, an in-vitro study also confirmed that Andrographolide has inhibitory potential against the NS3 protease of the Japanese encephalitis virus [34]. In these studies, the compound Andrographolide from Andrographis paniculata was predicted by the pkCSM tool and showed a negative result for toxicity analysis and was proven to be an efficient antiviral drug for human consumption.…”
Section: Discussionmentioning
confidence: 74%
“…The toxicity properties of the phytochemicals were predicted by using the web tool called pkCSM. It is one of the in silico software which predicts the toxicity caused by molecules to humans [32,34,35]. By using the pkCSM web tool, hepatotoxicity, AMES toxicity, hERG I inhibitor, max.…”
Section: Toxicity Predictionmentioning
confidence: 99%
See 1 more Smart Citation